2017
DOI: 10.1038/s41598-017-06923-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline diamond protects Zr cladding surface against oxygen and hydrogen uptake: Nuclear fuel durability enhancement

Abstract: In this work, we demonstrate and describe an effective method of protecting zirconium fuel cladding against oxygen and hydrogen uptake at both accident and working temperatures in water-cooled nuclear reactor environments. Zr alloy samples were coated with nanocrystalline diamond (NCD) layers of different thicknesses, grown in a microwave plasma chemical vapor deposition apparatus. In addition to showing that such an NCD layer prevents the Zr alloy from directly interacting with water, we show that carbon rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The obtained results demonstrated that after performance of the hot steam treatment at 900-1000 • C, the uncoated ZIRLO rods exhibited a higher hydrogen concentration (1166 ppm) compared to the ZIRLO rod protected by the diamond coating (164 ppm). The ratio of the hydrogen content in the hot steam-processed-uncoated ZIRLO and ZIRLO rods with diamond coating corresponds well to our previous results-after hot steam (for 1100 • C and 1200 • C) the uptake of hydrogen into uncoated ZIRLO was an order of magnitude higher than in the case of the diamond layer protected ZIRLO rods [19].…”
Section: Effect Of the Diamond Coating On The Hydrogen Uptake By Zirlo Surfacessupporting
confidence: 90%
See 2 more Smart Citations
“…The obtained results demonstrated that after performance of the hot steam treatment at 900-1000 • C, the uncoated ZIRLO rods exhibited a higher hydrogen concentration (1166 ppm) compared to the ZIRLO rod protected by the diamond coating (164 ppm). The ratio of the hydrogen content in the hot steam-processed-uncoated ZIRLO and ZIRLO rods with diamond coating corresponds well to our previous results-after hot steam (for 1100 • C and 1200 • C) the uptake of hydrogen into uncoated ZIRLO was an order of magnitude higher than in the case of the diamond layer protected ZIRLO rods [19].…”
Section: Effect Of the Diamond Coating On The Hydrogen Uptake By Zirlo Surfacessupporting
confidence: 90%
“…These changes, which strongly depend on the temperature and diamond content in the coating, support and also reduce corrosion of ZIRLO fuel rods. According to our previous accidental temperature tests of polycrystalline diamond coated nuclear rods [19] in 1000 • C hot steam/water (60 min) and in 1100 • C (60 min) and 1200 • C (20 min) hot steam/water, the corrosion of diamond layer coated nuclear tubes was always lower than the corrosion of uncoated rods subjected to the same treatment [19]. In [19,21,24], we presented that the diamond-coated Zr nuclear fuel rods were protected against accidental temperature hot steam/water corrosion due to the fact that the carbon diffused from the diamond coating into ZrO2, changing its physical property of semi conductivity.…”
Section: Corrosion Of the Diamond-coated Zirlomentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high thermal stability of these hydride phases also makes them a matter of concern for reactor safety due to the potential for hydrogen storage and release during loss-of-coolant conditions and core meltdown. Palliative measures such as increasing the enthalpy of formation of δ-ZrH by microstructure tailoring [108], or by hindering H diffusion in Zr oxide by selective alloying in the clad [109,110], have been proposed for future candidate materials in novel nuclear fuel designs.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical resolution of an optical microscope, not taking into account optical aberrations, using white light, is about 0.2 microns. However, more realistically, the measurement of films with a thickness of less than one micron is difficult and features consistent uncertainty [50][51][52][53].…”
Section: Optical Microscopymentioning
confidence: 99%